RELIGIUSITAS, MARGIN LEVEL, DAN KUALITAS LAYANAN TERHADAP KEPUTUSAN NASABAH MELAKUKAN TAKE OVER PEMBIAYAAN - Malkan Malkan; Abdul Jalil (FINANSIA : Jurnal Akuntansi dan Perbankan Syariah, 2023)
The customer's decision to take over is based on the intention of facilitating pre-existing financing, by adding installments or looking for a lower interest rate. Research to determine and analyze the influence of religiosity, margin level, and quality of service on customer decisions to take over financing. The study sample was 108 people and used purposive sampling. Using multiple linear regression analysis. Research shows that simultaneously the variables of religiosity, margin level, and service quality have a significant effect on customers' decisions to take over financing at Islamic Banks with an adjusted R Square value of 0.507 equal to 50.7%. The remaining variables that were not included in model (e) amounted to 49.3%. Partially, religiosity and margin level have a significant effect on customer decisions, and service quality does not affect customer decisions.